2020
DOI: 10.1039/d0sc02076a
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry of three-center, four-electron bonds

Abstract: The factors determining the symmetry and the fundamental nature of the three-center, four-electron bonds are assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 42 publications
6
70
0
Order By: Relevance
“…+ complex, allowing formation of a slightly destabilized yet symmetric halogen bond. As the core of 1 is more adaptable than the previously studied bidentate bis(pyridine)-type donors, 15,22 11,12,23 The former prefers an asymmetric geometry, with a distinct covalent and a distinct secondary bond, while the latter is centrosymmetric. Three-center halogen bonds have occasionally been referred to as coordinative bonds.…”
Section: å In Its Monomeric [N•••i•••n]mentioning
confidence: 99%
See 1 more Smart Citation
“…+ complex, allowing formation of a slightly destabilized yet symmetric halogen bond. As the core of 1 is more adaptable than the previously studied bidentate bis(pyridine)-type donors, 15,22 11,12,23 The former prefers an asymmetric geometry, with a distinct covalent and a distinct secondary bond, while the latter is centrosymmetric. Three-center halogen bonds have occasionally been referred to as coordinative bonds.…”
Section: å In Its Monomeric [N•••i•••n]mentioning
confidence: 99%
“…11, 15-20, 22, 24-27 Moreover, the three-center [N•••Ag•••N] + bond of silver(I) in the bis(pyridine) complex has been shown to be similar to the analogous Au(I) complex in solution, the solid state and in silico. 23 The analysis of statistical trends from X-ray crystallographic observations, using data obtained from the Cambridge Structural Database (CSD) indicated that the bis(pyridine) complexes of other transition metals, such as Hg(II), Cd(II), Te(III), Er(III), Zn(II), Gd(III), Mn(II), Fe(II), Ni(II), Cr(II), and Rh(I) also form linear and symmetric bis(pyridine)metal(I-III) three-center complexes with comparable geometries. 23 Accordingly, the analyses of iodine(I) and silver(I) complexes are expected to provide general conclusions to compare the bonding of halonium and transition metal complexes.…”
Section: å In Its Monomeric [N•••i•••n]mentioning
confidence: 99%
“…Another challenge announced here concerns asymmetric [NXN] + systems since the symmetrical systems containing the halogen, X, are known rather from various studies [ 48 ]. For example, the experimental NMR spectroscopic and crystal structure studies as well as the theoretical calculations were performed recently on the systems containing halogen cation as well as other cations between nitrogen centres, i.e., the [NZN] + systems where Z + = H + , Li + , Na + , F + , Cl + , Br + , I + , Ag + and Au + [ 52 ]. Two series, one of bis(pyridine) entities and the second one containing the (1,2-bis(pyridin-2-ylethynyl)benzene) structure were considered [ 52 ].…”
Section: The Case Of Halogen Bondsmentioning
confidence: 99%
“…For example, the experimental NMR spectroscopic and crystal structure studies as well as the theoretical calculations were performed recently on the systems containing halogen cation as well as other cations between nitrogen centres, i.e., the [NZN] + systems where Z + = H + , Li + , Na + , F + , Cl + , Br + , I + , Ag + and Au + [ 52 ]. Two series, one of bis(pyridine) entities and the second one containing the (1,2-bis(pyridin-2-ylethynyl)benzene) structure were considered [ 52 ]. In all cases the symmetrical arrangements are observed, only for Z + = H + and F + the asymmetric systems occur; this concerns both above-mentioned series.…”
Section: The Case Of Halogen Bondsmentioning
confidence: 99%
See 1 more Smart Citation